The Rebased Nigerian Gross Domestic Product (GDP): A Paradox of Realities - OLU, JEREMIAH; Mathew, Grace Obaje; Luke, Balogun Victor; Ojodomo, Audu Abel (IJRDO - Journal of Business Management, 2021)
This study titled ‘The Rebased Nigerian Gross Domestic Product (GDP): A Paradox of Realities’ is motivated by the fact that recent rebasing of the Nigerian Gross Domestic Product now positions the Nigerian economy as the largest in Africa ahead of South Africa and Egypt, and that in spite of this huge GDP, there is a clear evidence of a co-existence of abject poverty on the one hand and abundant human and natural resources on the other. This paradox economist referred to as “resource curse”. The study made use of secondary data sourced from the Central bank of Nigeria (CBN) and the National Bureau of Statistics (NBS) to show forth the significance of GDP rebasing and the evidence of this paradox. Using appropriate descriptive statistical tools our study revealed that though the rebased GDP holds great potentials for the Nigerian economy, it is not a true reflection of the realities on ground in terms of impact on the welfare of Nigerian citizens. Therefore, the study recommended that the Government should create a support mechanism for the very poor population in order to boost their consumption capacity and make them active players in the economy, as a strategy to create market for local industry.